2016
DOI: 10.1007/s00109-016-1439-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptional regulation of hypoxia-inducible factor-1α by arsenite under normoxia and hypoxia: involvement of Nrf2

Abstract: Arsenite (As(III)) is widely distributed in nature and can be found in water, food, and air. There is significant evidence that exposure to As(III) is associated with human cancers originated from liver, lung, skin, bladder, kidney, and prostate. Hypoxia plays a role in tumor growth and aggressiveness; adaptation to it is, at least to a large extent, mediated by hypoxia-inducible factor-1α (HIF-1α). In the current study, we investigated As(III) effects on HIF-1α under normoxia and hypoxia in the hepatoma cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 70 publications
5
19
0
Order By: Relevance
“…Furthermore, PI3K can upregulate the HIF-1 α protein translation [48]. Studies have been also showing that the induction of the Nrf2 pathway augments HIF-1 α signaling [49]. Consistent with these reports, our results found that PI3K specific inhibitor LY294002 significantly restored the sensitivity of MCF-7/ROS cells to ADM. More importantly, HIF-1 α and Nrf2 were manifested as the downstream targets of overactivated PI3K/Akt pathway, while they were both responsible for the overexpression of P-gp in MCF-7/ROS cells.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, PI3K can upregulate the HIF-1 α protein translation [48]. Studies have been also showing that the induction of the Nrf2 pathway augments HIF-1 α signaling [49]. Consistent with these reports, our results found that PI3K specific inhibitor LY294002 significantly restored the sensitivity of MCF-7/ROS cells to ADM. More importantly, HIF-1 α and Nrf2 were manifested as the downstream targets of overactivated PI3K/Akt pathway, while they were both responsible for the overexpression of P-gp in MCF-7/ROS cells.…”
Section: Discussionsupporting
confidence: 90%
“…We confirmed these genomic findings in multiple cell lines, we identified a functional NRF2 binding site (i.e., an antioxidant response element, or ARE) approximately 32 kilobases upstream of HIF1A , and we found that oncogenic NRF2 mutations are associated with high HIF1A expression in multiple cancer types. These findings are consistent with recent work suggesting NRF2 plays a role in HIF1A expression [31] , [32] , and our work lends further support to a model in which NRF2 is a direct regulator of HIF1A transcription.…”
Section: Introductionsupporting
confidence: 93%
“…Although much research effort has focused on the post-translational regulation of HIF1α levels, largely because the rapid increase in HIF1α protein stability is central to the adaptive response to hypoxia because [47] , [48] , several groups have recognized that regulation of HIF1α expression is also important [45] , [49] , [50] , [51] , [52] . And, importantly, HIF1A expression has been linked to ROS in multiple settings: HIF1A mRNA is upregulated by ROS-inducing mutations in mouse lung carcinoma cells, by multiple sources of ROS in pulmonary artery smooth muscle cells, by chemotherapeutic-induced ROS, and by the ROS-inducer arsenite [32] , [45] , [53] , [54] . Overall, in combination with this previously published work, these results demonstrate that ROS can activate HIF1A expression in multiple cellular contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Another redox regulated transcription factor which regulates the HIF system is Nrf2 (Nfe2l2; nuclear factor (erythroid-derived 2)-like 2) [111]. Nrf2 is known to contribute to intermediary and xenobiotic metabolism, bile production, as well as liver regeneration, and carcinogenesis [112], [113], [114], [115], [116], [117], [118].…”
Section: Hif Phds Redox and Zonationmentioning
confidence: 99%